The Adoption of Blue Ocean Strategy to Sustain Competitive Advantage in the Syrian Food Industry - Aram Hanna Massoudi; Mohamed Essam Ahmed (UKH Journal of Social Sciences, 2021)
This study aims to detect the extent of adoption of the Blue Ocean Strategy in the Syrian ‎food industry companies and its role in improving its competitive advantage. Syrian ‎Companies need to shape their blue ocean strategy in accordance with consumer value, ‎price, cost, and adoption. This permits them to construct a feasible business model and ‎ensure that profits from the blue ocean is created. The study used descriptive-analytical ‎approach. The data were composed of a questionnaire distributed to 293 personnel ‎working in 85 Syrian food companies. Statistical Package for Social Science (SPSS 22) were ‎applied to analyze the data. The result showed there are a substantial interest by Syrian ‎food companies to adopt Blue Ocean strategy indicators in its operations. Also, there was ‎a significant relationship between the adoption of Blue Ocean Strategy and the ‎improvement of sustainable competitive advantage for the investigated companies. The ‎researchers suggested that Syrian companies should emphasize on the importance of the ‎innovation indicator and its role in producing new brands and creating markets free of ‎competition which sequentially contributes to increase in the company's market share. The ‎study achieves a qualitative benefit for both researchers and academics about the concept ‎of BOS because it is the first study that introduces the BOS and its impact on sustainable ‎competitive advantage in Syrian‎.